Little Finger with Subungual Osteochondroma: Diagnostic Approach and Treatment - Adanas, Cihan; Yılmaz, Omer; Duymus, Mahmut; Bozkurt, Alper (Fırat University, 2011)
Osteochondromas are the most frequently occurring bone tumors. However, they rarely arise in subungual locations. Clinically they appear as slowgrowing masses causing deformity of the overlying nail. Here we evaluate a case of subungual osteochondroma of the little finger that is very rare in the literature. Radiological findings were diagnostic, and local tumor excision was the treatment of choice. The diagnosis was performed by a plain radiographic film and the lesion was completely detached from the nail bed. If a dense lesion detected in little finger of a young patient, it should be bear in mind that the lesion may be osteochondroma and complete removal may be chosen instead of biopsy.

Osteokondromlar nadir görülen kemik tümörleridir. Bazen subungual bölgede gelişebilirler. Klinik olarak, yavaş büyüyen kitleler şeklindedirler ve geliştiği tırnak yatağında deformiye neden olurlar. Biz burada literatürde nadir yayınlanmış olan serçe parmakta subungual osteokondrom vakasını sunuyoruz. Radyolojik bulgular tanısaldı, tedavi lokal eksizyonla gerçekleştirildi. Tanı direkt grafi filmi ile kondu ve lezyon tırnak yatağından tamamıyla çıkarıldı. Genç hastada serçe parmakta dens lezyon tespit edilirse lezyonun osteokondrom olabileceği akılda tutulmalı ve biyopsi almak yerine total eksizyon yapmanın uygun olacağı önerilmiştir.
Serçe Parmakta Subungual Osteokondrom:Tanısal Yaklaşım ve Tedavi